Health promotion through digital media during the pandemic: The learner at the centre of the teaching-learning process - Gutiérrez Sánchez, María Constanza Lidia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The teaching work during the pandemic, has made changes in their work methodology, the virtual classroom experience of the subject of microbiology presented involves the fifth semester students of the area of health area, of de high school Benito Juarez Garcia, in this, the student must learn to investigate, design, and implement a proposal for dissemination on the etiology and prevention of diseases caused by microorganisms. Therefore, due to the health contingency, dissemination was by digital means through Blogs.